The effect of profitability, capital structure and leverage on financial performance with audit committee as moderating variable audit committee as a moderating variable - Surya Pratama, Muhammad Dhanu; Bambang Subiyanto (SEAN Institute, 2024)
This research aims to analyze and obtain empirical evidence regarding Profitability, Capital Structure, Leverage on Financial Performance with the Audit Committee as a moderating variable. The novelty of this research is to test whether the audit committee can moderate the effect of profitability, capital structure, and leverage on financial performance. The data used in this study are panel data of 11 companies listed on the Indonesia Stock Exchange for the period 2018-2022. Data processing is done with WarpPLS 8.0. The results showed that Profitability, Capital Structure, Leverage had a significant effect on Financial Performance with the significance of P-Value = 0.001, 0.001 and 0.011 smaller than 0.050. Respectively, The Audit Committee can be a moderated variable for the relationship between Profitability and Capital Structure on Financial Performance with a significance value of P-Value = 0.002 & 0.007 respectively, while the Audit Committee didn't moderate the relationship between Leverage and Financial Performance with a significance value of P-Value = 0.197